Ukraine e-Government Assessment - World Bank (World Bank, Washington, DC, 2018)
Electronic Government (e-government) is among the main bases for improving public administration and service delivery in Ukraine. To effectively support enhanced developmentoutcomes, it requires a systemic and coordinated approach and parallel advancement of various components of digitalization. The purpose of this assessment is to identify issues and opportunities to consolidate, enhance and accelerate the electronic government reform in Ukraine. It informs and serves as a foundation for the prioritization and development of future areas of engagement of the broader e-government reform.Efforts to advance the implementation of e-government activities have not been properly sequenced and have been uncoordinated.To assess governance e-transformation this report introduces a comprehensive methodology – Electronic Government’s Governance Outline (hereafter Assessment) – that was developed by the team and is used for the first time. This assessment reflects the progress and status against various benchmarks of e-government, grouped in 18 dimensions and spread among 5 areas.The Ukraine assessment is a first attempt at bringing together the technical perspective of digitalization with the treatment of the agency problem underlaying the essence of governance. Recognizing the challenges and complexity of reforms in this area, the report outlines key priorities for future focus by policymakers and implementers in setting up specific strategies for addressing weaknesses and advancing reforms. The assessment, which was performed through desk review of policy and regulatory framework, interviews and structured surveys of key stakeholders, reveals a pattern of disproportional development of the system. The report discusses three foresight scenarios as alternatives to the “status quo”.The scenarios reflect different approaches to addressing identified vulnerabilities of e-government in Ukraine. Implementing many of the good practices will be a challenge in the short-term. Next steps should ideally focus on reforms that prioritize consolidation of datacenters. Implementing a centralized policy for ICT procurement requires strong political will and high-level support. The first manifestation of such political support could be clear definition of the stakeholder roles and, most importantly, separation of implementation from policymaking.